2023
DOI: 10.18805/ijar.bf-1611
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Storage Periods on the Internal and External Quality Characteristics of White and Brown-Shell Table Eggs in Saudi Arabia

Abstract: Background: The eggs of hens are an essential source of protein, a food that meets human needs and provides the body with amino acids, metallic elements and vitamins that promote its health. The research aims to study the influence of storage period and strain and the interaction between them on components and internal and external quality traits of commercially produced brown and white-shell eggs. Methods: A total of 180 eggs were randomly collected from both types. It was kept for 0, 15 and 30 days at temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The researchers documented that egg quality decreased with increasing storage time [3,6]. Our results showed that refrigerated storage and three kinds of vinegar coating had the greatest impact on maintaining egg quality factors, particularly haugh unit and yolk index, which are primary indicators of egg quality [17].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The researchers documented that egg quality decreased with increasing storage time [3,6]. Our results showed that refrigerated storage and three kinds of vinegar coating had the greatest impact on maintaining egg quality factors, particularly haugh unit and yolk index, which are primary indicators of egg quality [17].…”
Section: Resultsmentioning
confidence: 60%
“…Table eggs' qualitative, chemical, functional, and microbiological features are influenced by the environment variables such as the bird's age, food, season, temperature, transportation, storage time, and heat exposure [6]. An egg's internal composition and structural changes start as soon as it is laid.…”
Section: Introductionmentioning
confidence: 99%
“…Brown eggs scored substantially higher (p<0.01) than W hite Lohmann eggs. According to Hassanin and Gabal (1990) (Monira et al, 2003;Zita, 2009;Murshed et al, 2023). When stored for 0, 10, 20 and 30 days, egg weight reduced considerably (Table 2).…”
Section: Resultsmentioning
confidence: 91%